Why too soon? Predictors of time to diabetic peripheral neuropathy among newly diagnosed diabetes mellitus patients: a multicenter follow-up study at health-care setting of Ethiopia - Gebiso Roba Debele; Samuel Abdisa Kuse; Bilisumamulifna Tefera Kefeni; Abdi Geda; Wakuma Wakene Jifar; Keno Melkamu Kitila; Mohammedamin Hajure (BMC, 2023)
Abstract Background Due to the rising number of diabetic patients, the burden of diabetic peripheral neuropathy (DPN) is clearly posing a major challenge to the long-term viability of the health-care system. Despite this, most DPN epidemiological research in eastern Africa, including Ethiopia, has so far been limited to survey studies. Thus, we determined the incidence of DPN and its predictors among diabetic patients in tertiary health-care setting of southwest Ethiopia. Methods A multicenter retrospective follow-up study was carried out on 567 randomly selected diabetic patients. Data were entered using Epi-Data v4.6 and analyzed using R v4.0.4. The survival curves were estimated using the Kaplan-Meier, and compared using Log-rank test between groups of categorical variables. The PHA were evaluated using the Schoenfeld residuals test. Multivariable Gompertz proportional hazard model was used to examine the predictors of DPN at 5% level of significance. Results Overall, of 567 DM patients 119 developed DPN with an incidence rate of 3.75, 95%CI [3.13, 4.49] per 100 PY. About 15.13% and 69% of DPN cases occurred within 2 and 5 years of DM diagnosis, respectively. In the multivariable Gompertz PH model, being female [AHR = 1.47; 95% CI (1.01, 2.15)], T2DM [AHR = 3.49 95% CI (1.82, 6.71)], having diabetic retinopathy [AHR = 1.9 95% CI (1.25, 2.91)], positive proteinuria [AHR = 2.22 95% CI (1.35, 3.65)], being obese [AHR = 3.94 95% CI (1.2, 12.89)] and overweight [AHR = 3.34 95% CI (1.09, 10.25)] significantly predicts the future risk of DPN. Conclusion Nearly, 7 in 10 of DPN cases occurred within short period of time (5 year) of DM diagnosis. Being female, T2DM, DR, positive proteinuria, obese and overweight significantly predicts the risk of DPN. Therefore, we recommend screening and early diagnosis of diabetes with its complication. While doing so, attention should be given for DM patients with DR and positive proteinuria at baseline.